2016
DOI: 10.1007/s13280-016-0853-y
|View full text |Cite
|
Sign up to set email alerts
|

Using certified timber extraction to benefit jaguar and ecosystem conservation

Abstract: The jaguar Panthera onca requires large areas of relatively intact habitats containing adequate amounts of prey to survive. Since a substantial portion of jaguar range occurs outside of strict protected areas, there is a need for economic incentives for habitat conservation, which carefully managed selective logging can provide. Forest Stewardship Council and Pan European Forest Council certifications intended to regulate wood extraction to maintain the ecological functions of forests require evidence of biodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 72 publications
1
7
0
1
Order By: Relevance
“…The jaguar in particular is at risk of displacement, population decline, and local extinction (Menezes et al, 2021). Previous studies documented healthy and rich ecosystems in the Chiquitano Dry Forest (Rumiz et al, 2002;Arispe et al, 2007;Venegas et al, 2010;Polisar et al, 2016;Jansen et al, 2020). Our results give further support that the Chiquitano Dry Forest in Bolivia, often embedded in a mixed land use area, harbors a significant, but still largely understudied population of jaguars.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The jaguar in particular is at risk of displacement, population decline, and local extinction (Menezes et al, 2021). Previous studies documented healthy and rich ecosystems in the Chiquitano Dry Forest (Rumiz et al, 2002;Arispe et al, 2007;Venegas et al, 2010;Polisar et al, 2016;Jansen et al, 2020). Our results give further support that the Chiquitano Dry Forest in Bolivia, often embedded in a mixed land use area, harbors a significant, but still largely understudied population of jaguars.…”
Section: Discussionsupporting
confidence: 83%
“…Camera traps allow for constant, non-invasive, long-term biomonitoring of jaguars to measure shifts in population structure, or to estimate population sizes (Silver et al, 2004). Previous studies imply that the Chiquitano Dry Forest harbors a substantial but widely understudied population of jaguars and their prey (Rumiz et al, 2002;Arispe et al, 2007;Venegas et al, 2010;Polisar et al, 2016). Here, we report on an ongoing camera trapping survey established in 2017 (Jansen et al, 2020).…”
Section: Introductionmentioning
confidence: 89%
“…NGOs can also support and/or lead ecological monitoring of certified forests, helping to evaluate the ecological impact and provide recommendations for improved management. For example, the Wildlife Conservation Society and partners evaluated certified forests in Guatemala, Nicaragua, French Guiana, and Bolivia, concluding that at these specific sites certified forest management has been effective in conserving jaguars and their habitats (Polisar et al, 2016). Studies of this nature can assist in making the case for the continuance of forest management regimes, especially in the face of relentless pressure from alternative land uses including cattle grazing and oil palm cultivation.…”
Section: Ngos To the Rescue?mentioning
confidence: 99%
“…Secondary growth is avoided by jaguars in comparison to tall forests, so we assumed that animals in those areas would be displaced the surrounding region (Conde et al, 2010). We excluded regions with selective logging (either regular or conventional) because it was found that these species still occur in areas with selective logging (Polisar et al, 2017). With this information, we settled for areas in which we believed we could not find jaguars.…”
Section: Background Datamentioning
confidence: 99%